Improved dye-sensitized solar cell performance with hedgehog-like shaped ZnO nanorods grown using ZnO nanoparticles seed layer. (2022) - Yuliasari, F.; Aprilia, A.; Hidayat, R.
Abstract: We have investigated the preparation of ZnO nanorods (ZnO-NRs) with a hedgehog-like structure by hydrothermal method and the working performance of dye-sensitized solar cell (DSSC) based on this ZnO-NRs electrode. ZnO-NRs were grown from ZnO nanoparticles (ZnO-NPs) seed layer. Scanning Electron Microscopy (SEM) images show that ZnO-NPs seed layer produced a hedgehog-like shape ZnO-NRs . The X-Ray Diffraction (XRD) characterization results show that the resulted ZnO-NRs have a good crystallinity with the diffraction pattern of hexagonal wurtzite ZnO. The optical absorbance spectra show a high dye absorption for ZnO-NRs with a hedgehog-like shaped structure. The power conversion efficiency of the cell using a hedgehog-like ZnO-NRs is around 2.35%, which is larger than the cell with all-vertically aligned ZnO-NRs that produce efficiency of about 1.86%. The intensity-modulated photovoltage spectroscopy (IMVS) characterization indicates that the effective total diffusion length to reach FTO becomes smaller and the recombination loss is reduced for DSSC with a hedgehog-like ZnO-NRs. This study shows that hedgehog-like ZnO-NRs can improve the cell perfomace of DSSC based on ZnO-NRs.